1992
DOI: 10.2307/1485991
|View full text |Cite
|
Sign up to set email alerts
|

Cenozoic Foraminiferal and Dinoflagellate Cyst Biostratigraphy of the Central North Sea

Abstract: We present a detailed Cenozoic biostratigraphy for Paleogene bathyal and Neogene neritic strata, north of 55? in the central North Sea, and offshore mid-Norway, using both foraminifera and dinoflagellate cysts. Construction of the zonations was assisted by the quantitative stratigraphic methods RASC and STRATCOR. Eight Paleogene and four Neogene interval zones of benthic and some planktonic foraminifera are defined. These zones involve the average last occurrence of 64 taxa present in a minimum of 7 of 33 well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…(MD-177; MD-184; MD-85; see Table 1 The agglutinated benthonic foraminifer Karreriella conversa (Eggerellidae), found in MD-208 255, has an Upper Cretaceous-Lutetian range ( Fig. 2; Gradstein et al, 1988;. 209…”
mentioning
confidence: 99%
“…(MD-177; MD-184; MD-85; see Table 1 The agglutinated benthonic foraminifer Karreriella conversa (Eggerellidae), found in MD-208 255, has an Upper Cretaceous-Lutetian range ( Fig. 2; Gradstein et al, 1988;. 209…”
mentioning
confidence: 99%
“…During the early 1980s, several biostratigraphic schemes based on agglutinated foraminifers were devised for the Paleogene of the North Sea region (Gradstein and Berggren, 1981;King, 1983;Gradstein et al, 1988). It became apparent that a number of EoceneOligocene DWAF species occur throughout the North Sea, Norwegian Sea, and Labrador Sea, suggesting that they may be useful for correlation purposes throughout the northern part of the North Atlantic.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have further refined the taxonomy and biostratigraphy of Norwegian Sea DWAF Kaminski et al, 1990;Osterman and Spiegler, 1996;Kaminski and Geroch, 1997;Nagy et al, in press;Gradstein and Kaminski, 1997). Quantitative studies of biostratigraphic data from 33 North Sea and Norwegian Sea exploration wells have yielded a refined biostratigraphic zonation of the area using DWAF and other microfossils (Gradstein et al, 1988;Gradstein et al, 1992Gradstein et al, , 1994Gradstein and Bäckström, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Rare finds of Praecystammina globigerinaeformis in Paleocene sediments in Hole 801A extends the range of this species to the lowermost Tertiary in abyssal assemblages of low latitudes. Gradstein et al (1988) observed a very similar form, which they determined as Cystammina aff. globigeriniformis, in bathyal Paleocene wells of the central North Sea.…”
Section: Foraminifersmentioning
confidence: 95%